DEVELOPMENT OF E-KELURAHAN SERVICES IN DARAT SEKIP SUB DISTRICT, PONTIANAK CITY - Ayu Widowati Johannes; Oklin Riinan Winowoda; Valentino Christ Vowell Van Bayu (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2021)
This study aims to analyze the development of E-kelurahan services at Darat Sekip Sub District Pontianak City by using qualitative descriptive analysis of sub district services using electronic access. This research is studied using the concept of sub district functions which are analyzed from various aspects, such as interface, navigation, content, reliability and technical. The results show that the benefits of implementing the e-kelurahan application can be implemented well with the support of state civil servants in Darat Sekib sub district who are able and understand the use of the e-kelurahan application, although there are still obstacles that must be corrected immediately to be better.